Pengaruh Lingkungan Kerja, Kepemimpinan dan Kompensasi Terhadap Kepuasan Kerja Karyawan Pada PT. Sumber Sawit Makmur - Sinaga, Marisa Zahra; Pratiwi, Nuning; Rusmewahni, Rusmewahni; Hartanto, Bobby (STIE Bina Karya, 2024)
This research aims to determine the influence of the work environment, leadership and compensation on employee job satisfaction at PT. Sumber Palm Makmur. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to employees at PT. Sumber Palm Makmur. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests are normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis tests namely T test and F test. The results of SPSS in this research are that the work environment influences job satisfaction, leadership influences on job satisfaction, compensation has no effect on job satisfaction, work environment, leadership, and compensation have a simultaneous effect on job satisfaction.